My Brother's Keeper? The Association Between Having Siblings in Poor Health and Wealth Accumulation. (February 2014) - Heflin, Colleen M.; Chiteji, Ngina
When confronted with the economic costs of addressing a serious health problem, many American households do not possess the ability to deal with the crises on their own and may turn to family members for help. Using longitudinal data from the Panel Study of Income Dynamics, we examine if the level of wealth held by individuals is related to the health problems of their siblings. We find evidence that having a sibling who has experienced a health problem decreases the amount of wealth that some families have. The research has implications for the existing literatures on altruism and kin networks, as it sheds some light on the nature of altruism that prevails in U.S. families and on how kinship networks matter. Because of its focus on the consequences of health problems, the research also has implications for public policy discussions about the health care system and social insurance more generally.